Study of character and diversity of vegetation (cultivated plants) in Al-aaras Tourst Island / Baghdad (Baghdad Science Journal, 2011)
Vascular plants that have been identified during the study seasons in the Island. The cultivated plants were 126 species belong to 103 genera and to 49 families of the year 2001-2002 . The natural vegetation in this Island has been subjected to a total disturbance and subsidence due to the comprehensive turbidity of the Island environment.Number of names of that natural vegetation has been mentioned in the study within the weed plants.The results of the study of the period of flowering and their attitudes show clear seasonal differences. During the cold months of winter, the number of the cultivated and the natural plants was at the rate of 15%.These kinds of flowers require high level of care to increase their numbers. While in the spring season the number of the flowering of cultivated plants reach 64%.As for the type and the nature of the Flora, the annual species were 64%, while the trees were 18%. The perennial herbs and shrubs were 11% and 13% successively. The study of the analysis of vegetation clarifies that Cynodon dactylon has the higher level of coverage and frequency among the other cultivated plants.